2020
DOI: 10.1149/09810.0393ecst
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Electrolysis Conditions for Ti Film Electrodeposition from LiF – LiCl Eutectic Molten Salt

Abstract: The optimum conditions for electrodeposition of compact, smooth and adherent Ti films in LiF-LiCl-Li3TiF6 at 823 K were investigated. The Li3TiF6 was formed in situ in the melt via comproportionation reaction between Li2TiF6 and Ti powder. The solubility of Li3TiF6 was confirmed to be higher than 7.1 mol% by cyclic voltammetry and ICP-AES measurement. Galvanostatic electrolysis was conducted on Ni plate substrates at various concentrations of Li3TiF6 (0.55, 2.6, 7.1 mol%) and cathodic current density (50-1200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…CsF-CsCl-WO 3 melts.-In our previous study on the electrodeposition of Ti coatings in molten LiF-LiCl-Li 3 TiF 6 , the growth of crystal grains could be effectively suppressed and smoother deposits were obtained by lowering the temperature from 923 to 823 K. 17,18 Thus, in the present study, the temperature was reduced by utilizing CsF-CsCl eutectic melts with the aim to prepare smoother W coatings. Figure 9 shows cyclic voltammograms at a Au flag electrode in molten CsF-CsCl-WO 3 (2.0 mol% WO 3 added) at 823 and 873 K. As observed for the KF-KCl-WO 3 (2.0 mol% added) at 923 K, CsF-CsCl-WO 3 exhibited a cathodic current peak at approximately 1.3 V vs Cs + /Cs at all temperatures, indicating the electrodeposition of W. However, the peak current density at 823 K was too small compared with 873 K. This result suggested that the solubility of WO 3 at 823 K was smaller than 2.0 mol%.…”
Section: Resultsmentioning
confidence: 77%
“…CsF-CsCl-WO 3 melts.-In our previous study on the electrodeposition of Ti coatings in molten LiF-LiCl-Li 3 TiF 6 , the growth of crystal grains could be effectively suppressed and smoother deposits were obtained by lowering the temperature from 923 to 823 K. 17,18 Thus, in the present study, the temperature was reduced by utilizing CsF-CsCl eutectic melts with the aim to prepare smoother W coatings. Figure 9 shows cyclic voltammograms at a Au flag electrode in molten CsF-CsCl-WO 3 (2.0 mol% WO 3 added) at 823 and 873 K. As observed for the KF-KCl-WO 3 (2.0 mol% added) at 923 K, CsF-CsCl-WO 3 exhibited a cathodic current peak at approximately 1.3 V vs Cs + /Cs at all temperatures, indicating the electrodeposition of W. However, the peak current density at 823 K was too small compared with 873 K. This result suggested that the solubility of WO 3 at 823 K was smaller than 2.0 mol%.…”
Section: Resultsmentioning
confidence: 77%
“…In our previous study on the electrodeposition of Ti films in molten LiF-LiCl-Li3TiF6, the growth of crystal grains could be effectively suppressed and smoother deposits were obtained by lowering the temperature from 923 K to 823 K (10,11). Thus, in the present study, we attempted to lower the temperature by utilizing CsF-CsCl eutectic melts.…”
Section: Csf-cscl-wo3 Meltsmentioning
confidence: 92%